Ultrasensitive Freestanding and Mechanically Durable Artificial Synapse with Attojoule Power Based on Na‐Salt Doped Polymer for Biocompatible Neuromorphic Interface. (21st August 2021) - Hu, Luodan; Li, Lei; Chang, Kuan‐Chang; Lin, Xinnan; Huang, Pei; Zhang, Shendong
Abstract: The human brain, with high energy‐efficient and parallel processing ability, inspires to mitigate power issues perplexing von Neumann architecture. As one of the essential components constructing the human brain, the emulation of biological synapses exploiting electronic devices consuming power at a biological level lays the foundation for the implementation of energy‐efficient neuromorphic computing. Besides, signal matching between biologically‐related stimuli and the driving voltage of artificial synapses helps to realize intelligent neuromorphic interfaces and sustainable energy. Here, ultra‐sensitive artificial synapse stimulated at 1 mV with energy consumption of 132 attojoule/synaptic event is demonstrated. Biological signal matching and low power application are realized simultaneously based on sodium acetate (NaAc) doped polyvinyl alcohol (PVA) electrolyte. The biphasic current, which comprises the electrical‐ and ion‐mediation current component, contributes to enrich synaptic functions compared to monophasic synaptic behavior. Moreover, freestanding NaAc‐doped PVA membrane functions as both dielectric layer and mechanical support and facilitates to achieve flexible, transferable artificial synapse, which maintains functional stability at an ultralow voltage and power even after bending tests. Thus, encompassing superior sensitivity, low energy, and multiple functionalities with flexible, self‐supported, biocompatible property, takes a step to construct energetically‐efficient, complex neuromorphic systems for wearable, implantable medicines as well as smart bio‐electronic interfaces. Abstract : Based on sodium acetate doped polyvinyl alcohol electrolyte, synaptic devices with superior sensitivity at 1 mV and ultra‐low energy consumption down to 132 attojoule/synaptic event are realized simultaneously. Moreover, a flexible, transferable, and freestanding artificial synapse, which maintains functional stability at ultralow voltage after bending, is achieved.